Brain Drain: Out of Bound Mobility of International Students in Bangladesh - Ahmed, Rashed (RADINKA JAYA UTAMA PUBLISHER, 2025)
The phenomenon of brain drain, particularly the out-of-bound mobility of international students, has emerged as a critical issue for developing nations like Bangladesh. This article explores the causes, consequences, and potential strategies to mitigate brain drain, focusing on the emigration of skilled individuals and students pursuing higher education abroad. Utilizing a combination of literature reviews and case studies, this study underscores the socio-economic, educational, and policy-driven factors contributing to brain drain in Bangladesh. It concludes with actionable recommendations to foster a more sustainable approach to human capital retention and development.